Evaluation of compliance and adherence to medications in diabetic and/or hypertensive patients during the lockdown period and the effect of COVID-19 lockdown on blood glucose levels and blood pressure levels - Renuka BG; Kandagaddala Yaswath; Shweta R Chittawadgi; Yogeshwar; Sushma HK; Narendranath Sanji (Asian Journal of Medical Sciences, 2024)
Background: To contain the COVID-19 pandemic, a nationwide lockdown was imposed, which affected the lives of people with diabetes and hypertension as the patients were not able to regularly follow up with the doctor.